2005
DOI: 10.1182/blood-2004-08-3373
|View full text |Cite
|
Sign up to set email alerts
|

Punish the parent not the progeny

Abstract: Chronic myeloid leukemia (CML) is sustained by a rare population of primitive, quiescent, BCR-ABL ؉ cells and represents an excellent example of a malignancy in which tumor-initiating cells represent the key to disease eradication. CML is also the first malignancy for which targeted therapy has replaced conventional chemotherapy. Within a vast excess of proliferating progenitor cells that express breakpoint cluster region-abelson (BCR-ABL) and are exquisitely sensitive to the tyrosine kinase inhibitor imatinib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
104
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(105 citation statements)
references
References 56 publications
0
104
0
1
Order By: Relevance
“…2 Tyrosine kinase inhibitors (TKIs) have revolutionized the natural history of CML, with overall survival and event-free survival rates of 88% and 83%, respectively for imatinib-treated patients, and low frequency of transformation into blastic phase. 3 Quiescent primitive CML CD34 þ cells are insensitive to TKIs, however, and these cells persist even when complete responses are achieved, 4 leading to disease recurrence following discontinuation of TKIs in a fraction of CML patients. 5 The quiescent CML cells are in general resistant to a wide variety of proapoptotic stimuli, 6 implying unique mechanisms of protection from imatinib and other insults that induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…2 Tyrosine kinase inhibitors (TKIs) have revolutionized the natural history of CML, with overall survival and event-free survival rates of 88% and 83%, respectively for imatinib-treated patients, and low frequency of transformation into blastic phase. 3 Quiescent primitive CML CD34 þ cells are insensitive to TKIs, however, and these cells persist even when complete responses are achieved, 4 leading to disease recurrence following discontinuation of TKIs in a fraction of CML patients. 5 The quiescent CML cells are in general resistant to a wide variety of proapoptotic stimuli, 6 implying unique mechanisms of protection from imatinib and other insults that induce apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The cancer stem cell hypothesis has been substantiated and is exemplified in many types of leukemia, in which a stem or progenitor cell origin has been characterized [235,236]. In the case of BCR-ABL, accumulating evidence suggests that the target cell for transformation is a hematopoietic stem cell rather than a committed progenitor cell [65,237,238]. Interestingly, a recent study by Tothova et al, (2007) reported an elevated level of reactive oxygen species (ROS) restricted to the hematopoietic stem cell (HSC) compartment of mice deficient in three members of the FoxO subfamily (FoxO1, FoxO3 and FoxO4) [162].…”
Section: Targeting the "Right" Population Of Tumor Cells In Anti-cancmentioning
confidence: 99%
“…Disturbingly, BCR-ABL transcripts coding for mutations in the kinase domain have been detected even in some patients who have achieved a complete cytogenetic response, suggesting a link between resistance and disease persistence [62,63]. Together with mathematical models that take into account the bi-phasic response to imatinib as well as a continued need for imatinib therapy [64], all these observations have led to the conclusion that imatinib is unable to target the quiescent BCR-ABL-positive stem cell population, and thus cannot completely eliminate the disease [65].…”
Section: Clinical Resistance To Imatinib and The Need For Alternativementioning
confidence: 99%
See 1 more Smart Citation
“…The bone marrow microenvironment is believed to have a role in protecting LSCs and CML cells from TKIsinduced apoptosis (6). CXCL12, also called stromal cellderived factor-1 (SDF-1), a chemokine produced by bone marrow stromal cells (BMSC), signals through the cognate chemokine receptor CXCR4, which is broadly expressed by normal and malignant cells of hematopoietic and nonhematopoietic origin (7).…”
Section: Introductionmentioning
confidence: 99%